FIRST HIGHER EDUCATIONAL UNIVERSITY OF JIZZAKH (Web of Technology: Multidimensional Research Journal, 2024)
This article talks about the Jizzakh State Pedagogical Institute, which was founded in 1974 in the Jizzakh oasis, how the university was founded, the material and technical base, research work and the educational process. The article also talks about the general activities of the university over half a century.